Characterization of Bioactive Compounds from Acacia concinna and Citrus limon, Silver Nanoparticles’ Production by A. concinna Extract, and Their Biological Properties - Ibrahim Ahmed Shaikh; Uday M. Muddapur; Zabin K. Bagewadi; Sneha Chiniwal; Mohammed M. Ghoneim; Mater H. Mahnashi; Fahad Alsaikhan; Deepak Yaraguppi; Francois N. Niyonzima; Sunil S. More; Basheerahmed Abdulaziz Mannasaheb; Amer Al Ali; et al. (Molecules, 2022)
The applications of bioactive compounds from medicinal plants as therapeutic drugs are largely increasing. The present study selected the bioactive compounds from Acacia concinna (A. concinna) and Citrus limon (C. limon) to assess their phytochemicals, proteins, and biological activity. The plant material was collected, and extraction performed as per the standard procedure. Qualitative analysis was undertaken, and identification of functional organic groups was performed by FTIR and HPLC. Antibacterial, anticancer, antioxidant, antihyperglycemic, antihyperlipidemic, and inhibition kinetics studies for enzymes were performed to assess the different biological activities. Flavonoids and phenols were present in a significant amount in both the selected plants. A. concinna showed significant antimicrobial activity against Z. mobilis, E. coli, and S. aureus, with minimum inhibition zones (MIZ) of 24, 22, and 20 mm, respectively. C. limon strongly inhibited all the tested pathogenic bacteria with maximum and minimum MIZ of 32 and 17 mm. A. concinna silver nanoparticles also exhibited potent antimicrobial activity. Both extracts showed substantial antioxidant, antihyperlipidemic, antidiabetic, anticancer (MCF-7), and anti-urease (antiulcer) properties. To conclude, these plants can be used to treat hyperlipidemia, diabetes, cancer, and gastrointestinal ulcers. They can also serve as antimicrobial and antioxidant agents. Thus, the studied plants must be exploited cost-effectively to generate therapeutic drugs for various diseases.